Нелинейная контактная задача применительно к зацеплению прямых зубьев - Попов, А. П.; Попова, Л. А.; Медведовский, А. М.; Савенков, О. И. (НТУ "ХПИ", 2015)
Впервые представлены результаты теоретических исследований контактной прочности традиционных зубчатых передач с прямыми зубьями с учётом нелинейной взаимосвязи между упругими перемещениями (деформациями) зубьев и возникающими при этом напряжениями. При этом определены зависимости максимальных контактных напряжений σH и полуширины b₀ прямоугольной площадки контакта. Показано, что величина напряжений σH в рассматриваемом случае несколько превышает таковую, имеющую место при отсутствии указанной нелинейности. В соответствии со сказанным величина b₀, наоборот, несколько превышает аналогичную ширину, характерную для случаев отсутствия рассматриваемой нелинейности.

Contact strength of teeth is one of the main criteria working capacity of gears. Calculation of gearing on the contact strength is carried out by a well-known formula of Hertz in relation to the model of contact between two elastic compression cylinders with radii and p1 P2 at the pitch and involves determining the maximum contact stress. For the first time the results of theoretical analysis’s of contact strength of traditional gearings with the straight teeth taking into account non-linear correlation between elastic displacements (deformations) of teeth and arising stresses have been presented. By that the dependences of the maximum contact stresses σН and the semi width b0 of the right-angled contact area have been determined. His shown that the value of stresses σН in this case slightly exceeds the value taking place in the absence of non-linearity. In accordance with stated above b0 on the contrary slightly exceeds the analogous width which is typical for the cases of absence of the abovementioned non-linearity.
Non-linear contact problem conformably to straight tooth system
Keywords: зубчатая передача; контактное напряжение; нагрузка; gearing; teeth; contact stress; load capacity